HASIL BUAH MANGGA PADA BEBERAPA FREKUENSI PEMBERIAN DAN KONSENTRASI PUPUK DAUN YIELD OF MANGO AT SEVERAL APPLICATION FREQUENCIES AND CONCENTRATIONS OF FOLIAR FERTILIZER - , Sakhidin (Pembangunan Pedesaan, 2009)
The aim of this research was to study the effect of application frequencies and oncentrations of foliar fertilizer on yield of mango. The research was conducted in mango orchard belong to UPTD Balai Pengembangan Benih Hortikultura dan Aneka Tanaman (BPBHAT) Instalasi Kasugengan, Cirebon Regency from July to November 2007. This research used Completely Randomized Design with three replicates. Factors tested were the application of foliar fertilizer, i.e., one, two, and three times; and concentrations of the fertilizer, i.e., 0, 0.1, and 0.2%. Each unit of experiment consisted of one tree; each tree was taken 20 panicles as sample. Result of the research showed that the application of 3 times gave the highest number and weight of harvested fruit per tree. Concentration of the 0.2% fertilizer gave the highest yield of mango. There was no interaction effect of the application and concentration on all observed variables.